2015
DOI: 10.1177/1538574415611234
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Level and Bleeding Risk During Catheter-Directed Thrombolysis Using Tissue Plasminogen Activator

Abstract: A fibrinogen level <1.5 g/L during thrombolysis was not associated with an increased bleeding risk. However, larger dose and longer duration of thrombolysis were associated with increased bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Even if adjuvant therapy was possible, and the procedure time tended to be shorter in CDT, CBT seemed to have the advantages of a lower CDT duration and rt-PA dosages than conventional CDT. Several studies have examined whether the risk factors for bleeding risk during CDT are related to the duration and dosages of CDT used [18,19]. Approximately one-half of patients with ALI did not require adjunctive CDT, and the present study supported the major potential advantage of CBT, which, if successful as a stand-alone treatment, obviates the requirement for CDT with a concomitant reduction in the risk of hemorrhagic complications.…”
Section: Discussionsupporting
confidence: 65%
“…Even if adjuvant therapy was possible, and the procedure time tended to be shorter in CDT, CBT seemed to have the advantages of a lower CDT duration and rt-PA dosages than conventional CDT. Several studies have examined whether the risk factors for bleeding risk during CDT are related to the duration and dosages of CDT used [18,19]. Approximately one-half of patients with ALI did not require adjunctive CDT, and the present study supported the major potential advantage of CBT, which, if successful as a stand-alone treatment, obviates the requirement for CDT with a concomitant reduction in the risk of hemorrhagic complications.…”
Section: Discussionsupporting
confidence: 65%
“…However, they also markedly increase the risk of bleeding [ 19 ]. In addition, emergency treatment of CVDs with t-PA greatly increases the risk of bleeding [ 20 ]. Therefore, there is an urgent need for safer and more effective drugs to replace current treatments.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a significantly higher rate of bleeding if the fibrinogen level was <150 mg/dL [ 16 ]. On the contrary, a study performed by Lee et al, which examined 49 procedures, found that there was no significant increased risk of bleeding in patients with fibrinogen levels less than 150 mg/dL, despite larger total doses of TPA and longer duration of therapy [ 17 ]. The prospective PURPOSE trial with 241 patients undergoing catheter-directed thrombolysis found that there was no statistically significant difference in major or minor bleeding in patients with fibrinogen >100 mg/dL or <100 mg/dL ( p = 0.108) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%